MULTICENTRIC RETICULOHISTIOCYTOSIS (MRH): A CASE REPORT ON A RARE DESTRUCTIVE ARTHRITIS - Saira Bano,; Tayyeba Khursheed,; Mohammad Khalid Bosan,; Sadia Khurshid, (Journal of Ayub Medical College Abbottabad, 2023)
Multicentric Reticulohistiocytosis is a rare disorder of unknown aetiology which affects skin and joints predominantly. There are no specific laboratory investigations for diagnosis. Diagnosis can be made clinically and on histopathological basis. There is no consensus on treatment. We report a case from Pakistan with classical presentation who did well on methotrexate and low dose steroids. Prompt diagnosis and early treatment may save from significant disability.